PERBEDAAN KINERJA SKPD YANG BELUM DAN SUDAH MELAKUKAN PENILAIAN RISIKO (STUDI PADA DINAS KESEHATAN GIANYAR) - Mediani, Komang Indah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.02.TAHUN 2017, 2017)
The performance of Public sector is influenced by an uncertainty, giving a positive influence (opportunity), or negative influence (risk). The high change and demands for a quality service for government institution, so that a risk assessmen is needed. The study aims to determine differences in Gianyar regency health office performance before and after doing a risk assessment. The research is a case study with quantitative data in the form of secondary data, the performance of health services, (as measured by the Minimum Service Standards). The data is examined with parametrik paired sample t test. The sensitivy analisys is done in health service in Badung Regency to convince that the risk is a cause for an increase performance. The results of the examination shows that there is no difference performance before and after doing the risk assessment in health service in Gianyar Regency. This is supported by the sensitivity test showed different results.
Keywords: Performance, The Risk Assessment Health Service, Sensitivity Analysis.